2011
DOI: 10.1039/c1ee02421c
|View full text |Cite
|
Sign up to set email alerts
|

Carbon coated textiles for flexible energy storage

Abstract: This paper describes a flexible and lightweight fabric supercapacitor electrode as a possible energy source in smart garments. We examined the electrochemical behavior of porous carbon materials impregnated into woven cotton and polyester fabrics using a traditional printmaking technique (screen printing). The porous structure of such fabrics makes them attractive for supercapacitor applications that need porous films for ion transfer between electrodes. We used cyclic voltammetry, galvanostatic cycling and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
339
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(358 citation statements)
references
References 29 publications
4
339
1
1
Order By: Relevance
“…Flexible supercapacitors have been developed previously to maintain mechanical integrity during packaging, 11 and for integration with smart textiles. 12 The goal, here, is to develop strong, stiff, multifunctional supercapacitors, capable of full structural function, ultimately akin to a normal fibrereinforced polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible supercapacitors have been developed previously to maintain mechanical integrity during packaging, 11 and for integration with smart textiles. 12 The goal, here, is to develop strong, stiff, multifunctional supercapacitors, capable of full structural function, ultimately akin to a normal fibrereinforced polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…Strong, flexible yarn-based supercapacitors are attractive as power sources for miniaturized electronic devices [13][14][15][16] such as micro-robots, wearable electronic textiles and implantable medical devices, as they can have small volumes and could be easily integrated into variously shaped structures. However, technical challenges have limited the development of strong, flexible and weavable yarns and fibres having attractive supercapacitor performance.…”
mentioning
confidence: 99%
“…Example of MEMS Energy harvester device [6] as carbon nanotubes or graphene that are revolutionizing the electronic world. Researchers have already shown that with NT it is possible to create thin film batteries Kuwata et al [28], Ogawa et al [44] printable on top of substrates, or creating a smart fibers that can store energy (so called E-textiles) Gu et al [18], Jost et al [25]. Furthermore, in the literature there are presented many demonstrators of energy harvesting devices that are able to "'harvest"' energy from many different physic sources (such as mechanical vibrations, temperature gradients, electro-magnetic radiations, etc) and transform it into electrical energy.…”
Section: Nanotechnologies For Energy Related Issuesmentioning
confidence: 99%